Effect of Needle Valve Motion On Cavitation And Gas Ingestion At End Of Injection. Issue 16 (10th December 2021) - Wen, Hua; Ma, Jinglong; Jiang, G.; Lee, Y.
ABSTRACT: In this paper, the cavitation and gas ingestion in a custom-made transparent nozzle were observed using a visual experimental platform of a transparent nozzle. Based on the Two-Fluid Model and dynamic grid overlapping, the evolution mechanism of the cavitation and gas ingestion in a diesel engine nozzle was analyzed at the end of injection, and the influence of three different velocities of the needle valve motion was analyzed. The results demonstrated that cavitation in the orifice preceded that in the sac, and the cavitation was mainly concentrated in the sac. As the needle valve seating velocity increased, the amount of cavitation and gas ingestion in the nozzle increased. Furthermore, as the amount of gas ingestion increased, the time of gas ingestion inception was delayed, and the value varied nonlinearly from 0.48 ms (0.2 m/s) to 0.13 ms (1.0 m/s). A dimensionless parameter C N was deduced by theoretical analysis to describe the cavitation extent in the orifice at the end of injection. This study provides a theoretical basis for further analysis of the mechanisms of cavitation and gas ingestion as well as the effect of the needle valve velocity on cavitation and gas ingestion.